Interactive and unimodal relationships between plant biomass, abiotic factors, and plant diversity in global grasslands - Marie Spohn; Sumanta Bagchi; Jonathan D. Bakker; Elizabeth T. Borer; Clinton Carbutt; Jane A. Catford; Christopher R. Dickman; Nico Eisenhauer; Anu Eskelinen; Nicole Hagenah; Yann Hautier; Sally E. Koerner; et al. (Communications Biology)
Abstract Grasslands cover approximately a third of the Earth’s land surface and account for about a third of terrestrial carbon storage. Yet, we lack strong predictive models of grassland plant biomass, the primary source of carbon in grasslands. This lack of predictive ability may arise from the assumption of linear relationships between plant biomass and the environment and an underestimation of interactions of environmental variables. Using data from 116 grasslands on six continents, we show unimodal relationships between plant biomass and ecosystem characteristics, such as mean annual precipitation and soil nitrogen. Further, we found that soil nitrogen and plant diversity interacted in their relationships with plant biomass, such that plant diversity and biomass were positively related at low levels of nitrogen and negatively at elevated levels of nitrogen. Our results show that it is critical to account for the interactive and unimodal relationships between plant biomass and several environmental variables to accurately include plant biomass in global vegetation and carbon models.